Fatty acid metabolism in marine fish: Low activity of fatty acyl Δ5 desaturation in gilthead sea bream ( Sparus aurata ) cells - Tocher, Douglas R; Ghioni, Cristina (Lipids, 1999)
Marine fish are known to have an absolute dietary requirement for C20 and C22 highly unsaturated fatty acids. Previous studies using cultured cell lines indicated that underlying this requirement in marine fish was either a deficiency in fatty acyl Δ5 desaturase or C18-20 elongase activity. Recently, Ghioni et al. (Biochim. Biophys. Acta, 1437, 170-181, 1999) presented evidence that in turbot cells there was low activity of C18-20 elongase whereas Δ5 desaturase had high activity. In the present study, the fatty acid desaturase/elongase pathway was investigated in a cell line (SAF-1) from another carnivorous marine fish, sea bream. The metabolic conversions of a range of radiolabelled polyunsaturated fatty acids that comprised the direct substrates for Δ6 desaturase ([1-14C]18:2n-6 and [1-14C]18:3n-3), C18-20 elongase ([U-14C]18:4n-3), Δ5 desaturase ([1-14C]20:3n-6 and [U-14C]20:4n-3) and C20-22 elongase ([1-14C]20:4n-6 and [1-14C]20:5n-3) were utilized. The results showed that fatty acyl Δ6 desaturase in SAF-1 cells was highly active and there was substantial C18-20 elongase and C20-22 elongase activities. A deficiency in the desaturation/elongation pathway was clearly identified at the level of the fatty acyl Δ5 desaturase which was very low, particularly with 20:4n-3 as substrate. In comparison, the apparent activities of Δ6 desaturase, C18-20 elongase and C20-22 elongase were approximately 94-fold, 27-fold and 16-fold greater than that for Δ5 desaturase towards their respective n-3 polyunsaturated fatty acid substrates. The evidence obtained in the SAF-1 cell line is consistent with the dietary requirement for C20 and C22 highly unsaturated fatty acids in the marine fish, the sea bream, being primarily due to a deficiency in fatty acid Δ5 desaturase activity.